Storage management in DONA content routers. (2018) - Abidi, Amine; Gammar, Sonia Mettali
Information-centric networking (ICN) as an emerging paradigm for the future introduces a radical change in internet communications. It allows information access regardless of their location and it defines innovative concepts such as forwarding, name-based routing, security and caching. Many ICN architectures have been proposed over the past few years such as DONA, NetInf, CCN, NDN, publish-subscribe architecture, etc. In this paper, we focus especially on DONA, one of the first ICN architecture, and we analyse the required memory space to store routing states. Our study shows that today's technologies are not able to satisfy the content routing needs. Thus, we propose an enhancement of DONA called BADONA to deal with this problem. It uses the Bloom filter to drastically reduce the usage of the memory space. We evaluate our proposal performances and compare it with two ICN solutions: CCN and DHTChord to find out how these models scale when they are deployed over large networks. The obtained simulation results show that our solution reduces considerably the memory usage, and the decreasing ratio reaches the value of 40 with the standard Bloom filter version. Moreover, BADONA outperforms the other existing schemes.